Direct composite restorations to mask intrinsic staining: An eighteen-year follow-up - Mondelli, Rafael Francisco Lia [UNESP]; Soares,; Tostes,; Bombonatti, (My University, 2016)
In this case example, the use of direct composite resin allowed for a relatively simple, conservative treatment that provided excellent function and aesthetics, while preserving healthy dental tissue. The importance of continued follow-up and a periodic maintenance and minor repair process will ensure longevity of the restorations, the aesthetics, and the occlusion.